Zone-Based Tourism Planning Using Satellite Imagery - Angga Kurniawansyah; Dewi Susiloningtyas; Masita Dwi Mandini Manessa (The Journal of Indonesia Sustainable Development Planning, 2023)
Tourism planning serves as a strategic approach to mitigate and address the damage incurred by tourist attractions, such as the Tangkolak Bahari Center (TMC) mangrove ecosystem, which has experienced a loss of 2 hectares. The primary objective of this research is to formulate a zone-based tourism plan utilizing PlanetScope Dove-R sensor satellite imagery to provide spatial information specific to its application in December 2022. The methodology encompasses various techniques, including observation, structured interviews with tourists, focus group discussions involving tourism managers and local government representatives, digitization, and delineation. The result of research is Zones within the TMC tourist attractions, comprising Main and Supporting Space Plans, Primary and Secondary Circulation Plans, Avicennia, Rhizopora stylosa, and Sonneratia Conservation Vegetation Plans, as well as Plans for Nature, Conservation, Culinary Activities and Facilities, and Green Planning. Notably, the TMC tourist attraction remains viable, covering an area of 2.73 hectares in the West TMC and 1.79 hectares in the East TMC. It is imperative to underscore the importance of considering the sustainability of the mangrove ecosystem in utilizing these areas.